2009
DOI: 10.1007/s10531-009-9768-2
|View full text |Cite
|
Sign up to set email alerts
|

Urban realities: the contribution of residential gardens to the conservation of urban forest remnants

Abstract: Urbanization has destroyed and fragmented previously large areas of habitat. Small remnants that still exist in numerous cities will be unable to sustain many viable wild plant populations if they do not expand into the surrounding urban matrix. Residential gardens form a significant component of urban green space in many cities and therefore could play a role in redressing this problem. Our ecological and social scientific study examined factors influencing the dispersal and regeneration of 12 bird-dispersed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 41 publications
3
47
0
3
Order By: Relevance
“…One study found that residential neighbourhoods developed from forested areas had higher tree species richness and a greater proportion of native species compared to regions developed from prairie land [33]. Researchers have also suggested that the presence of remnant woodland located within or adjacent to residential areas can promote native species establishment and representation within the urban landscape [34,35].…”
Section: The Influence Of Remnant Woodland On Private Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…One study found that residential neighbourhoods developed from forested areas had higher tree species richness and a greater proportion of native species compared to regions developed from prairie land [33]. Researchers have also suggested that the presence of remnant woodland located within or adjacent to residential areas can promote native species establishment and representation within the urban landscape [34,35].…”
Section: The Influence Of Remnant Woodland On Private Propertiesmentioning
confidence: 99%
“…Home owner attitudes and preferences likely explain the diverse range of planting decisions; many social and economic factors taking place at the property-and neighbourhood-level can influence residential species diversity, such as income [38], education [39], ethnicity and nationality [40], and planting fads [41]. These patterns emphasize the potential for private yards and gardens to contribute to urban forest biodiversity [34,42]. It is thus important to consider how landscape conversion and development history could influence private property trees, particularly in the context of biodiversity management and enhancement.…”
Section: Home Owner Attitudes and Opportunities For Diversity Enhancementioning
confidence: 99%
“…Being the largest pheasant, reluctant to fly long distances, averse to humans and fragmentation of habitat is likely to have a detrimental effect on its survival. The selected parks of Delhi are very much disturbed in terms of human presence (Doody, 2010). The early morning and late evening hours should bedisturbance free in the parks so that the peafowl can roam and feed freely.…”
Section: Azadiracta Indica Prosopis Julifloramentioning
confidence: 99%
“…The urbanization process facilitates the establishment of exotic species through several mechanisms [40]. It reduces the diversity of native species by destroying and fragmenting large areas of habitat [41]. Secondly, exotic species are more likely to adapt to a variety of habitats in the city [42,43].…”
Section: Influences Of the Delimitations Of Study Areas On Comparingmentioning
confidence: 99%